PROSES PULANG BAINDUAK DI DESA LIPATKAIN KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Gustina, Ria; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Pulang Bainduak is another word of finding a foster mother for migrants who want to stay or want to marry one of the women in the village. Pulang Bainduak this makes a nomad has a tribe or has a mamak in Lipatkain Village with the intention to simplify all the affairs of the settlers and make it officially become the village community. The purpose of this research is 1) To know the History of Pulang Bainduak, 2) To know the procedure of Pulang Bainduak implementation in Lipatkain Village, 3) To know the positive and negative impact of Pulang Bainduak in Lipatkain Village, 4) To know the difference in the process of Pulang Bainduak each tribe in Lipatkain Village, 5) To find out what are the values contained in the Pulang Bainduak process in Lipatkain Village. In this study using qualitative methods, namely case studies, which will provide useful information for the public, especially science. The result of this research is that Lipatkain Village people still practice this tradition. This tradition is a hereditary tradition that has existed and was made in the days of Kings, this tradition through two processes, the first is a notice to the Tunganai, and the second process is a notice on Ninik Mamak, this process has many positive and negative impacts on the immigrants as well as the villagers themselves, one of whom helps the migrants if they get problems and for the villagers to keep their offspring, and the negative impacts are the lifelong ties to the tribal belt and the villagers of many immigrants bringing new cultures and their bad nature. Although it has different implementation in each tribe, it does not cause problems and debates among adat leaders and villagers themselves. And in this tradition there are several values contained therein, among them are religious, social, economic and cultural values. Keywords : Process Pulang Bainduak, Tradition, village Lipatkain